Choice of Appliance System in Adult Patients with Different Types of Malocclusion - DEEKSHEETHA, P.; FELICITA, A. SUMATHI; KAREEM, NASHRA (The journal of contemporary issues in business and government, 2021)
The aim of this study was to assess the choice of appliance system in adult patients namely those over 30 years of age with different malocclusions. There is an array of various orthodontic appliances used for the correction of different malocclusion in orthodontics. The appliances required for a particular type of malocclusion may not be well suited for another type of malocclusion. Orthodontic treatments are generally considered to cause discomfort to the patient and are time-consuming. Hence, the selection of the orthodontic appliance has a paramount role in the treatment of malocclusion. This was an University based cross sectional study conducted on male and female patients ranging from 30 to 50 years of age who reported for orthodontic treatment. The type of malocclusion, and the type of appliance used to correct the malocclusion present were assessed. The data was collected and tabulated in excel sheet, and exported to SPSS software for statistical analysis. The most common type of malocclusion in patients over 30 years of age who had reported for orthodontic treatment was class I malocclusion (81.43%), followed by class II malocclusion (17.14%) and the least number of patients had class III malocclusion (1.43% ). Among these patients, fixed appliances were the most commonly used treatment modality (95.7 %). There was a statistically significant difference in the prevalence of malocclusion in patients over 30 years of age with Class I malocclusion being the most prevalent (p=0.000). There was no statistical significance between the different types of appliances used for the correction of class I and class II malocclusion (p= 0.687). Among fixed appliance metal brackets were the most commonly used compared to ceramic and lingual brackets (p=0.000).